Pengembangan Kurikulum PAI Multi Development of Multicultural PAI Curriculum: Global and Comparative PAI - Azizah Intan Khairotun Nisa; Moh Miftachul Choiri; Mohammad Rohman Rifai; Krisnanda Alifia Ramadhanty; Wahyuadi Setyaningtyas Dewi Putri (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This article analyzes the development of a multicultural Islamic Religious Education (PAI) curriculum from a global and comparative perspective. Using library research, this study critically examines key works on multicultural education, global citizenship education, curriculum theory, and Indonesian academic studies on Islamic Religious Education (PAI). The analysis reveals that multicultural PAI should go beyond the normative delivery of religion toward contextual, dialogical, reflective, and transformative learning practices. A comparative examination of Malaysia, Egypt, Europe, and Finland reveals various curriculum orientations, including moderate integration, text preservation, interpretative dialog, and non-dogmatic humanistic education. Based on these findings, this article proposes a global-comparative reconstruction model that integrates Islamic values, cultural responsiveness, global citizenship, social justice, and the local realities of Indonesia. This model contributes to strengthening students' religious literacy while fostering inclusivity, tolerance, ethical awareness, and social responsibility. Multicultural Islamic Education (PAI) should be a transformative curriculum that prepares students to live peacefully in a pluralistic society, interconnected with love, wisdom, and a commitment to citizenship.